Structural Changes in Serbian Industry during Transition - Nikolić, Ivan; Zubović, Jovan (Industrija, 2013)
Transition is a complex process whereby a country in transition is stimulating structural changes wishing to achieve economic growth and improved social wellbeing. In this paper the authors aim to show that during transition in Serbia there such changes in the structure of manufacturing industry occurred, which resulted with only modest ​​growth that in fact was slower than in other transitional countries. By the means of theoretical and empirical approach – deductive methods, statistical and mathematical evaluation the authors have come to conclusion that structural changes did not improve industry branches like the hi-tech industry that contribute the most to PPP generation. At the same time, some low productive industries have gained on importance, therefore keeping the standard on the low levels without possibility to rapidly converge towards EU average, which was set as an ultimate goal of transition in Serbia.